2020
DOI: 10.1177/2325967120959330
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric and Adolescent Shoulder Instability: Does Insurance Status Predict Delays in Care, Outcomes, and Complication Rate?

Abstract: Background: Recurrent shoulder instability results from overuse injuries that are often associated with athletic activity. Timely diagnosis and treatment are necessary to prevent further dislocations and secondary joint damage. In pediatric and adolescent patients, insurance status is a potential barrier to accessing timely care that has not yet been explored. Purpose: To examine the effect of insurance status on access to clinical consultation, surgical intervention, and surgical outcome of pediatric and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
(18 reference statements)
0
26
1
Order By: Relevance
“… 15 , 18 Similarly, adolescents with shoulder instability have higher rates of bony pathology and anterior labral pathology, in addition to higher incidence of recurrent dislocation. 7 In this study, we evaluated the influence of anatomic risk factors. Data are abundant on the impact of findings such as younger age, skeletal immaturity, increased patellar height, and trochlear dysplasia on increasing risk of recurrent instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 18 Similarly, adolescents with shoulder instability have higher rates of bony pathology and anterior labral pathology, in addition to higher incidence of recurrent dislocation. 7 In this study, we evaluated the influence of anatomic risk factors. Data are abundant on the impact of findings such as younger age, skeletal immaturity, increased patellar height, and trochlear dysplasia on increasing risk of recurrent instability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the role of socioeconomic and characteristic factors in delays in care in pediatric and adolescent orthopaedic sports medicine. 5 , 7 , 12 , 15 , 16 , 18 Much of the literature demonstrates longer time to treatment in those with public or government-based insurance. To date, there is no evidence of similar trends in patients with patellar instability.…”
mentioning
confidence: 99%
“…Patel et al 34 retrospectively examined pediatric patients undergoing ACLR at a tertiary care children's hospital and found that government-assisted insurance status was associated with significant delays in definitive management of their injuries. Other studies have shown disparities in access to care for other sports-related conditions in pediatric and adolescent patients, including access to care for meniscal pathology 25,32 and shoulder instability, 22 as well as access to advanced diagnostic imaging modalities. 7 This study was not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder instability also falls within this trend. Hung et al examined a series of pediatric and adolescent patients with shoulder instability and found that patients with public insurance had to wait 5 times longer for initial evaluation, 4 times longer for MRIs, were twice as likely to have bony pathology, and had post-operative dislocation at higher rates (24.3%) [42].…”
Section: Pathology-specific Disparitiesmentioning
confidence: 99%